Antibacterial nanofibers of pullulan/tetracycline-cyclodextrin inclusion complexes for Fast-Disintegrating oral drug delivery - Hsiung, Emmy; Celebioglu, Asli; Chowdhury, Rimi; Kilic, Mehmet E.; Durgun, Engin; Altier, Craig; Uyar, Tamer (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Tetracycline isa widely used antibiotic suffering from poor water solubility and low bioavailability. Here, hydroxypropyl-beta-cyclodextrin (HP ss CD) was used to form inclusion complexes (IC) of tetracycline with 2:1 M ratio (CD:drug). Then, tetracycline-HP ss CD-IC was mixed with pullulan- a non-toxic, water-soluble biopolymer - to form nanofibrous webs via electrospinning. The electrospinning of pullulan/tetracyclineHP ss CD-IC was yielded into defect-free nanofibers collected in the form of a self-standing and flexible material with the loading capacity of ti 7.7 % (w/w). Pullulan/tetracycline nanofibers was also generated as control sample having the same drug loading. Tetracycline was found in the amorphous state in case of pullulan/tetracycline-HP ss CD nanofibers due to inclusion complexation. Through inclusion complexation with HP ss CD, enhanced aqueous solubility and faster release profile were provided for pullulan/tetracy cline-HP ss CD-IC nanofibers compared to pullulan/tetracycline one. Additionally, pullulan/tetracycline-H P ss CD-IC nanofibers readily disintegrated when wetted with artificial saliva while pullulan/tetracycline nanofibers were not completely absorbed by the same simulate environment. Electrospun nanofibers showed promising antibacterial activity against both gram-positive and gram-negative bacteria. Briefly, our findings indicated that pullulan/tetracycline-HPBCD-IC nanofibers could be an attractive material as orally fast disintegrating drug delivery system for the desired antibiotic treatment thanks to its promising physicochemical and antibacterial properties. (c) 2021 Elsevier Inc. All rights reserved.